Street food in Maputo, Mozambique: Availability and nutritional value of homemade foods - Sousa, S (2018)
Background: A nutrition transition is occurring in the urban areas of developing countries, where street food makes an important contribution to daily food intake. Aim: We aimed to characterise street food offer in Maputo, Mozambique, and to evaluate the nutritional composition of the most common homemade foods. Methods: A cross-sectional study was conducted in 2014. Streets in the surroundings (500 m buffer) of randomly selected public transport stops in KaMpfumu district, Maputo, were canvassed to identify all street food vending sites (n = 968). Information regarding vending site characteristics and the food offered was gathered through interview and observation. Samples (n = 80) of the most common homemade foods were collected for laboratorial analysis. Results: Most street food vending sites identified were stationary (77.4%) and sold exclusively industrial food (51.9%). Frequency of fruit, beverages and food other than fruit was 24.5%, 32.5% and 73.9%, respectively. Fried cakes were the most energy-dense (430 kcal/100 g), and richest in fats (21.0g/100 g) and carbohydrates (53.4 g/100 g). The richest sources of protein were the stewed meat/fish/liver dishes (10.711.6 g/100 g). Fried cakes showed the lowest sodium and potassium content (90 mg/100 g and 81 mg/100 g, respectively) whereas hamburgers exhibited the highest content of those micronutrients (455 mg/100 g and 183 mg/100 g, respectively). Stewed liver dishes presented the highest sodium/potassium ratio (11.95). Fried snacks presented the highest trans-fatty acid content (0.20 g/100 g). Conclusions: Street food in Maputo is abundant and scattered throughout the urban district, exhibiting high variability in the nutritional composition of homemade foods. Public health policies should be targeted to improve the street food offer, promoting nutrient-dense foods and the reduction of added salt. (c) The Author(s) 2018.